Factors influencing the professional identity of nursing interns: a cross-sectional study - Lihong Zeng; Qirong Chen; Sisi Fan; Qifeng Yi; Wenhong An; Huan Liu; Wei Hua; Rong Huang; Hui Huang (BMC Nursing, 2022)
Abstract Background Improving the professional identity of nursing intern is significant for enhancing the number of new registered nurses and easing the shortage of nursing personnel. The clinical internship is a key period for the formulation of professional identity. However, we know little about the factors influencing the nursing interns’ professional identity during clinical internship. Therefore, this study explore the influencing factors of nursing interns’ professional identity during clinical internship. This study will provide evidence and suggestions for generating effective strategies contributing to professional identity improvement of nursing interns. Methods This was a cross-sectional study. The convenience sampling was used to recruit 398 nursing interns from a teaching hospital in Hunan, China. The demographic characteristics information was collected by a self-developed questionnaire. The nursing interns’ professional identity and potential influencing factors (e.g., work atmosphere, teacher capacity) were measured by questionnaires with good psychometric properties. The appropriate indicators were used for descriptive statistics, and t test, analysis of variance, Pearson’s correlation analysis and multiple linear regression were used to analyse the influencing factors. Results In this study, the influencing factors of nursing interns' professional identity are education level, first choice of major, residential status, work atmosphere, and teacher capacity. The results showed that: (1) the nursing interns with a higher education level reported a lower level of professional identity; (2) the nursing interns whose first choice of major was not nursing discipline reported a lower level of professional identity; (3) the nursing interns live in rural areas (compared to urban areas) reported a higher level of professional identity; (4) the nursing interns in better work atmosphere reported a higher level of professional identity; (5) the nursing interns under the guidance of the teachers equipped with better teaching capacity reported a higher level of professional identity. Conclusion The education level, first choice of major and residential status are influence factors of nursing interns’ professional identity. The nursing educators need to pay attention to nursing interns whose first choice is not nursing, and in a bachelor program, who may have a lower level of professional identity. It is crucial to enhance the nursing interns’ professional identity by improve the work atmosphere and clinical teachers’ capacity, to promote nursing interns to choose nursing as a profession and reduce the shortage of nursing workforce.